2005
DOI: 10.1016/j.jvs.2005.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous laser therapy and radiofrequency ablation of the great saphenous vein: Analysis of early efficacy and complications

Abstract: GSV occlusion was achieved in >90% of cases after both EVLT and RFA at 1 month. We observed three cases of thrombus protrusion into the CFV after EVLT and recommend early duplex scanning in all patients after endovenous saphenous ablations. DVT prophylaxis may be considered in patients >50 years old. Long-term follow-up and comparison with standard GSV stripping are required to confirm the durability of these endovenous procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
156
6
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(181 citation statements)
references
References 23 publications
6
156
6
12
Order By: Relevance
“…All previous studies have reported that the greatest superiority of RF over EVLA is greater patient satisfaction. 12,[17][18][19] In our study, however, patient satisfaction was higher in the EVLA group, while better results for criteria such as intraoperative and postoperative pain, postoperative analgesic requirement, return to activity and return to work were obtained in the EVLA group. Of these, postoperative pain and time to return to activity were statistically significant (P < 0.035 and P < 0.001, respectively).…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…All previous studies have reported that the greatest superiority of RF over EVLA is greater patient satisfaction. 12,[17][18][19] In our study, however, patient satisfaction was higher in the EVLA group, while better results for criteria such as intraoperative and postoperative pain, postoperative analgesic requirement, return to activity and return to work were obtained in the EVLA group. Of these, postoperative pain and time to return to activity were statistically significant (P < 0.035 and P < 0.001, respectively).…”
Section: Discussioncontrasting
confidence: 55%
“…Publications generally report that both methods have the same levels of successful ablation, but that pain levels and rates of complications following RFA are lower compared to EVLA. 12,[16][17][18][19][20] However, these studies have generally used low wavelength laser. Several recent studies suggest that better results are achieved with higher laser wavelengths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sclerotherapy arm subjects had self-limiting mild post-procedural pain and cordlike induration along the GSV with slightly higher incidence of thrombophlebitis as reported in previous studies [13]. Deep vein thrombosis, pulmonary embolism, and anaphylaxis have been reported as serious complications of these endoluminal treatment modalities [20][21][22], but none of the patients in our study groups had these complications.…”
Section: Discussionsupporting
confidence: 72%
“…Studies comparing different catheterdirected techniques have been published; however many of them are retrospective studies [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%